Growth Adaptability of Cinnamomum burmanni (Nees & T. Nees) Blume, Toona sinensis (Juss.) M. Roem, Melia azedarach L., Swietenia macrophylla King, Magnolia sumatrana var. glauca (Blume) and Gmelina arborea Roxb. on Ex-C Mining Land at Jatiroke Village, Jatinangor Sub-District, Sumedang Regency - SILVIA (NIM : 11513020) , IDA
Revegetation is a way to restore the condition and improve the function of a land in order to function normally and sustainably. The success of revegetation is influenced by the type of plant used. This research aims to determine the type of plants that have a high adaptability to grow on ex-c mining land at Jatiroke Village, Jatinangor Sub-District, Sumedang Regency. The adaptation rates are measured based on the increase in plant’s height, stem diameter, number of leaves, biomass and CO2 absorption. Measurements were done for three months on six months old Cinnamomum burmanni, Toona sinensis, Melia azedarach, Magnolia sumatrana, Gmelina arborea and Swietenia macrophylla. After three months of obeservation, C. burmanni has the highest height increase (13.92 cm) and the highest number of leaves increase (52 leaves) among the six plant species that is observed, but the increase in diameter is the smallest, i.e. 0.29 cm. Species that have the largest increase in diameter is S. macrophylla (0.55 cm). Species that have the smallest increase in height and number of leaves respectively are G. arborea (6.6 cm) and M. sumatrana (2 leaves). Species that have the largest biomass at the end of observation is C. burmanni (31.62 g), while the smallest is M. sumatrana (8.79 g). Species that have the largest CO2 absorption is C. burmanni (259,95 x 10-4 g/seedling/hour), while the smallest is M. sumatrana (45,77 x 10-4 g/bibit/jam). Differences in plant’s growth adaptation are influenced by physiology of each species. The increase of height, diameter and number of leaves are influenced by the ability of nutrient absorption and the ability to do photosynthesis in each species. Plant’s biomass is influenced by the result of photosynthesis because it shows the efficiency and effectiveness of plant physiological processes in accumulating the result of photosynthesis. The absorption of CO2 is influenced by the number of stomata and the number of leaves in each species. In general, it can be concluded that C. burmanni has a higher adaptability compared to the other five species that is observed.